2017
DOI: 10.3390/su9091524
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of the Adoption of Agricultural Irrigation Technologies and the Economic Returns: A Case Study in Chaiyaphum Province, Thailand

Abstract: This empirical research investigates the factors influencing the adoption of three irrigation technologies using a probit statistical model: water wheel (WW), water pump (WP), and weir (WR) irrigation technologies as well as their economic returns per unit of rice cultivated area. The influencing factors were categorized into demographic, socioeconomic, topographical, institutional, and attitudinal factor groups by 207 rice-growers in the Chaiyaphum province in northeastern Thailand. The results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 25 publications
6
27
1
Order By: Relevance
“…Enhancing social capital among farmers by cooperative operation and maintenance of irrigation systems has been reported as playing an important role in encouraging users to adopt sustainable technologies for more efficient water use and increased crop production [82,83]. This is consistent with the findings of Chuchird et al (2017) [84], who reported that WUA membership was a significant factor in the adoption of irrigation technologies.…”
Section: Measures (N = 381) Number Of Farmers Adopting Adopters (%)supporting
confidence: 70%
“…Enhancing social capital among farmers by cooperative operation and maintenance of irrigation systems has been reported as playing an important role in encouraging users to adopt sustainable technologies for more efficient water use and increased crop production [82,83]. This is consistent with the findings of Chuchird et al (2017) [84], who reported that WUA membership was a significant factor in the adoption of irrigation technologies.…”
Section: Measures (N = 381) Number Of Farmers Adopting Adopters (%)supporting
confidence: 70%
“…Nduneseokwu et al [32] (p. 6) and Chuchird et al [75] (p. 2) used field surveys for data collection. Also, because the level of internet connection in Uganda is still poor, the field survey was the most appropriate way of reaching respondents as compared to an online survey.…”
Section: Design Of the Study And Sampling Distributionmentioning
confidence: 99%
“…Although the utility of farmers is not directly observed, the relationship between the expected utility and innovation adoption is postulated to be a function of the characteristics observed and a random disturbance term that arises from unobserved factors. The strand of literature on adoption group these observed factors into various categories: farmer characteristics, farm-specific factors, and institutional and innovational factors (Langyintuo and Mekuria, 2005;Saka and Lawal, 2009;Chuchird et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%